Movement of decaying quasi-2-day wave in the austral summer-time mesosphere - Cornelius Csar Jude H. Salinas; Dong L. Wu (Scientific Reports, 2024)
Abstract The quasi-2-day wave (Q2DW) is a large temperature disturbance in the austral summer-time mesosphere. Its decay-phase movement and phase-speed are poorly understood. Q2DW events observed by the microwave limb sounder (MLS) onboard the NASA Aura satellite reveal that during the temperature Q2DW’s decay-phase, the Q2DW temperature disturbance is still substantial, but its phase-speed reduces exponentially, on average, from around −70 to −20 m/s in around 30-days. Observations also reveal significant interannual variability in these phase-speed values. Q2DW events simulated by the extended Canadian middle atmosphere model (eCMAM) reveal that during the Q2DW decay-phase, the temperature Q2DW phase-speed is strongly correlated with the summer mesosphere easterly jet (SMEJ) wind values. eCMAM also shows that the phase-speed interannual variabilities partially reflect the interannual variabilities of the SMEJ. Planetary-wave diagnostics indicate that during the Q2DW’s decay phase, there is still an active transfer of momentum from the SMEJ into Q2DW. The model simulations therefore indicate that the SMEJ plays a substantial role in the decaying temperature Q2DW phase-speed variabilities observed by MLS. This adds to our knowledge of how the SMEJ affects the Q2DW.